Exogenous Riboflavin Application at Different Growth Stages Regulates Photosynthetic Accumulation and Grain Yield in Fragrant Rice - Yizhu Wu; Siren Cheng; Xinfang Ding; Xueer Lin; Sicheng Deng; Ligong Peng; Hua Tian (Agriculture)
Fragrant rice has high market value and is popular among consumers because of its pleasant fragrance. Plant growth regulators and trace elements can influence the yield and physiological indices of fragrant rice. Riboflavin, a vital component of plant vitamins, plays a crucial role in plant growth and development, and it is a water-soluble vitamin that is essential for sustaining normal photosynthesis and metabolic processes. However, the effects of riboflavin on nutrient accumulation and yield formation in fragrant rice have rarely been reported. Therefore, to further increase the yield and quality of fragrant rice, this study investigated the impact of the foliar application of riboflavin at different growth stages on nutrient accumulation and yield formation in two different genotypes of fragrant rice via a pot experiment. The experimental design consisted of three treatment groups, i.e., the T0 treatment group (control), which was sprayed with water; the T1 treatment group, which was sprayed at the booting stage; and the T2 treatment group, which was sprayed at the flowering stage; in all of these groups, 20 mg·L−1 riboflavin solution was used. The results revealed that the yields of the T1 and T2 treatments increased by 6.56–7.25% and 10.52–13.80%, respectively, compared with those of T0, which was attributed mainly to the increase in 1000-grain weight and grain filling. Furthermore, foliar spraying of riboflavin significantly increased the chlorophyll content, which resulted in the increased production of more total starch, soluble sugars, and sucrose and facilitated their transportation to the seeds. Moreover, applying riboflavin directly to the leaves increased the activity levels of the sucrose synthase (SS) and sucrose phosphate synthase (SPS) enzymes. Among the three treatments, the T2 treatment had the most pronounced effect. The results revealed that the foliar application of riboflavin could increase photosynthesis and promote the production of nonstructural carbohydrates, thereby increasing the total aboveground biomass of fragrant rice by 17.00–20.91% and 21.07–72.91% under the T1 and T2 treatments, respectively. Additionally, spraying riboflavin promoted rapid increases in the weight of fragrant rice seeds. In conclusion, foliar spraying of riboflavin during the flowering stage of aromatic rice can effectively enhance photosynthetic accumulation and yield, which is a promising physiological regulation strategy and provides new theoretical guidance for high-yield cultivation practices.